Gender Identity and Phenotypic Variation of Sex Chromosome Disorders: A Study at Center for Disorder of Sex Development in Indonesia - Azalia, Putri; Juniarto, Achmad Zulfa; Winarni, Tri Indah (Faculty of Medicine, Diponegoro University, 2024)
Background: Sex chromosome DSD (Disorder of Sex Development) can be caused by numerical or structural abnormality in sex chromosome, which will lead to the atypical development in phenotype and also psychosexual. Gender assignment often become the primary problem in management of individual with DSD.Objective: To describe gender identity and phenotype variability based on karyotype classification among sex chromosome DSD cases in Indonesia Methods: This study is a descriptive retrospective study. Analyzing gender identity, karyotype classification and phenotype data from medical record of patients with cytogenetic analysis results classified as sex chromosome DSD in CEBIOR over 18 years period from 2004 to 2022.Results: Data showed the sex chromosome DSD classification with karyotype 45,X and variant (without Y chromosome), constituted 43.7% (42/96) cases, 100 % (42/42) patients have female gender identity; 19.8% (19/96) cases had karyotype 45,X/46,XY or Turner variant mosaicism with Y chromosome, majority of patients have male gender identity 73.7% (14/19); 18.7% (18/96) cases had 47,XXY (Klinefelter syndrome) and variant, majority of patients have male gender identity in 88.9 % (16/18) cases; 11.4% (11/96) cases had 46,XX/46,XY karyotype, majority have male gender identity in 81.8 %(9/11) cases ; and 6 cases (6.25%) classified as others, 66.67% (4/6) cases all of which contain Y chromosome, have male gender identity.Conclusion: . This study shows the presence of Y chromosome in the karyotype support a male gender identity. Sex chromosome DSD constitute high karyotype diversity and wide phenotypic abnormalities that necessitates careful clinical and cytogenetic evaluation